(untitled) (Jurnal Sosial Ekonomi Pertanian, 2023)
Abstract Uncertainty in price movements will cause producers to find it difficult to make decisions at the time of production. One of the agricultural commodities in Indonesia that is currently the center of attention is oil palm. Agricultural Research and Development stated that Indonesian palm oil has developed into an important part of the world by occupying the first position as a producer of palm oil. The last five years have shown that palm oil price movements are quite volatile. The weakest conditions occurred in the middle of 2019 when the price of palm oil is at US 0.5/kg. Meanwhile, the strongest condition occurred in early 2014 at US 1/kg. Mistakes in making business decisions resulting from uncertain price movements will cause the potential of Indonesian palm oil in the world to decline. Through the ARCH/GARCH method, the description of price movements in Indonesian Palm Oil will be known, so that it will be easier for producers in preparing future business plans. The results showed that the ARCH (1) model was able to describe the volatility of CPO prices that occurred in Indonesia, where the forecast for CPO price volatility will be smaller in the following year. The results of this study indicate that CPO prices will be more stable and have a good impact on the CPO industry in Indonesia. These findings can be used as a basis for determining Indonesia’s CPO production policy. Keywords: ARCH/GARCH, Plam Oil, Volatility